Do economic integration and fiscal competition help to explain location patterns? - Christian Volpe Martincus (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
Do trade integration and fiscal competition contribute to shape the economic landscape? The answer is yes. This paper uses a theoretical model and an econometric analysis of Brazilian regional manufacturing employment data over the period 1990-1998 to address this question. Brazil is a natural case study because this country liberalized trade during the 1990s and their sub-national governments engaged in a fiscal dispute. Econometric results show that trade liberalization has had an impact on spatial developments and this effect is increasing over time. Moreover, subsidies also exert an influence, but their relative importance is falling.
Keywords: F12; F15; H32; H71; R12; R30; R58; 330; Economic Integration; Fiscal Competition; Location Patterns; Manufacturing Industries; Brazil